Ecophysiological comportment of the tropical CAM-tree Clusia in the field I. Growth of Clusia rosea Jacq. on St John, US Virgin Islands, Lesser Antilles - Ball, E (The New phytologist, 1991)
Clusia rosea Jacq. is abundant in the moist parts of the Caribbean island of St John (US Virgin Islands, Lesser Antilles) but relatively rare along the dry south coast. Three types of seedlings were encountered, terrestrial seedlings, seedlings growing as humus-epiphytes on other trees, and seedlings growing inside the tanks of the bromeliad Aechmea lingulata (L.) Baker. Free-living trees grow from terrestrial seedlings or from epiphytic seedlings strangling and shading their host trees. Leaf-Na+ levels were always low (1-4 mequiv I-1 tissue water); trees close to the shore were not affected by salinity. In leaves of mature C. rosea trees, levels of Ca2+ , Mg2+ and K+ were about 60-90, 40-50, 45-55 mequiv I-1 tissue water, respectively. Epiphytic seedlings tended to contain lower levels of these inorganic cations than seedlings growing terrestrially or in the tanks of Ae. lingulata. Epiphytic seedlings contained significantly less nitrogen than terrestrial seedlings. In the leaves of mature trees N-levels were independent of altitude and location on the island, but shaded leaves had significantly higher N-levels than exposed leaves. Light compensation point of photosynthesis in epiphytic seedlings performing C3 -photosynthesis was 17-5 (μmol photons m-2 s-1 ), photosynthesis was saturated at about 300μmol photons m-2 s-1 showing a maximum rate of CO2 -uptake of 2-3 μmol m-2 s-1